Weak sectors and weak ties? Labour dependence and asymmetric positioning in GVCs - Lorenzo Cresti; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Focusing on labour requirements incorporated into GVCs, in the following, we develop a novel, non conventional measure of learning capabilities, represented by knowledge embodied along the division of labour within global production networks. In order to capture the division of labour, and the ensuing division of embodied knowledge, we move from monetary flows of production, or value-added embodied, to labour embodied in the I-O linkages. We focus on mature economies as offshoring has been particularly in place there. After constructing a new indicator of Bilateral Net Labour Dependence, we estimate its relationship with a measure of performance of industries, namely, labour productivity, seeking to challenge the established findings generally reporting a positive effect of GVCs participation for sector-level productivity. Our conjecture is that being in a weak position in terms of (net) labour provision results in an overall weakening of the capabilities of the loosing productive structure. We corroborate the conjecture with a panel analysis of OECD countries and industries for the time period 2000-2014.
Keywords: F16; F6; J24; L6; O14; 330; Input-output; global value chains; international division of labour; dependency theory